2007
DOI: 10.1027/1614-0001.28.4.205
|View full text |Cite
|
Sign up to set email alerts
|

Holland's Secondary Constructs of Vocational Interests and Career Choice Readiness of Secondary Students

Abstract: Abstract. This study examined the relationship between the secondary constructs of Holland's (1997) theory of vocational interests and career choice readiness (career maturity) attitudes with 358 Swiss secondary students. The hypothesis was tested that the secondary constructs consistency, coherence, differentiation, and congruence are measures for the degree of vocational interest development. Thus, they should belong to the content domain in career choice readiness and should show meaningful relations to car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
1
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 35 publications
(52 reference statements)
8
72
1
11
Order By: Relevance
“…Several studies also investigated group differences in interest differentiation and found that female college students and career clients have generally more differentiated interests than males (Fouad & Mohler, 2004;Miner, Osborne, & Jaeger, 1997), students in eleventh grade show more differentiated Differentiated and Elevated Interests 5 interests than students in eighth grade (Hall, Kelly, & Van Buren, 1995) or that adjudicated adolescents showed lower differentiation than a normative sample (Glaser, Calhoun, Bates, & Bradshaw, 2003). No general differences were found among ethnic groups or between students with an immigration background to native-born students (Fouad & Mohler, 2004;Hirschi & Läge, 2007).…”
Section: Research On Interest Differentiationmentioning
confidence: 99%
“…Several studies also investigated group differences in interest differentiation and found that female college students and career clients have generally more differentiated interests than males (Fouad & Mohler, 2004;Miner, Osborne, & Jaeger, 1997), students in eleventh grade show more differentiated Differentiated and Elevated Interests 5 interests than students in eighth grade (Hall, Kelly, & Van Buren, 1995) or that adjudicated adolescents showed lower differentiation than a normative sample (Glaser, Calhoun, Bates, & Bradshaw, 2003). No general differences were found among ethnic groups or between students with an immigration background to native-born students (Fouad & Mohler, 2004;Hirschi & Läge, 2007).…”
Section: Research On Interest Differentiationmentioning
confidence: 99%
“…Većina istraživanja ustanovila je vrlo niske ili neznačajne povezanosti profesionalne zrelosti s mjerama diferenciranosti i konzistentnosti profesionalnih interesa (Guthrie i Herman, 1982;Hirschi i Läge, 2007;Miner, Osborne i Jaeger, 1997). Miner i sur.…”
Section: Diferenciranost I Konzistentnost Interesa Kao Mjera Profesiounclassified
“…Nalazi o pozitivnoj povezanosti diferenciranosti profesionalnih interesa i profesionalne zrelosti podupiru Hollandovu teoriju (1985) i slažu se s nalazima nekih prijašnjih istraživanja (Erwin, 1982;Guthrie i Herman, 1982;Luzzo, 1995i Hirschi i Läge, 2007. Dobivene povezanosti profesionalne zrelosti i diferenciranosti vrlo su niske, što je bilo i očekivano.…”
Section: Raspravaunclassified
See 2 more Smart Citations